ANALISIS PENGGUNAAN MYOB ACCOUNTING SOFTWARE PADA MAHASISWA AKUNTANSI DENGAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL - Andreuw Kristian Pantow; Barno Sungkowo; Esrie A. N. Limpeleh; Antonius Tandi (Universitas Muhammadiyah Malang, 2020)
This study aims to analyze the effect of perceived usage, perceived ease of use and attitudes on the behavior interest of accounting students in using the MYOB Accounting application with the Technology Acceptance Model approach developed by Davis (1989). Data collection was carried out through a survey with a questionnaire to accounting students at Manado State Polytechnic. Analysis of research data using Partial Least Square (PLS). The results showed that when students felt the benefits and convenience of using the MYOB Accounting application for the process of preparing financial reports, it made them have the attitude to accept the use of the application. Furthermore, the perceived benefits of using the application and the positive attitude of students towards the use of MYOB Accounting affect their intention to use the application. On the other hand, the findings of this study do not prove the effect of ease of use of applications on the intention to use MYOB Accounting as a means of making financial reports.